Contrasting models of female reproductive tract in four o'clocks (Nyctaginaceae) - Nores, María Jimena (2015)
PREMISE OF THE STUDY: In angiosperms, several carpel tissues are specialized to facilitate pollen-tube elongation to achieve fertilization. We evaluated the possible evolutionary pathways of the diverse female reproductive tracts in Nyctaginaceae. METHODS: We studied the anatomy of a range of species representing diff erent tribes, using light, fl uorescence, scanning electron, and transmission electron microscopy. KEY RESULTS: Stigmas have multicellular, multiseriate papillae, except for Boerhavia diff usa with unicellular papillae. The styles are solid, with a strand of transmitting tissue linking the stigma with the ventral ovary wall. In Allionia , Boerhavia , and Mirabilis , the transmitting tissue branches into two independent tracts at the base of the ovary and continues across the lateral margins of the funicle to the micropyle; it is composed of cells with thick walls surrounded by abundant extracellular matrix. Bougainvillea , Pisonia , and Pisoniella have a diff use transmitting tissue and an obturator, a proliferation of cells covered by a layer of secretory papillae that encloses the funicle, placenta, and ventral wall of the gynoecium and contacts with the micropyle. CONCLUSIONS: We propose two models of female reproductive tract, (A) one in which an obturator is absent and the transmitting tissue is compact and branched and (B) one in which an obturator is present and the transmitting tissue is diff use. On the basis of character optimization, we hypothesize that model B represents the ancestral (plesiomorphic) condition in the family and model A originated once during evolution, within the tribe Nyctagineae.